An Econometric Evaluation of a Generalized Consumer Surplus Measure: The Mineral King Controversy - Cicchetti, Charles J.; Fisher, Anthony C.; Smith, V. Kerry (Econometrica, 1977)
Charles J. Cicchetti, Anthony C. Fisher, V. Kerry Smith, An Econometric Evaluation of a Generalized Consumer Surplus Measure: The Mineral King Controversy, Econometrica, Vol. 45, No. 4 (May, 1977), p. 1041